2022
DOI: 10.1177/02692155221105586
|View full text |Cite
|
Sign up to set email alerts
|

Art skill-based rehabilitation training for upper limb sensorimotor recovery post-stroke: A feasibility study

Abstract: Objective The objective of this study was to assess the feasibility of delivering Art skill-based Rehabilitation Training (ART), a novel upper limb motor training program, to patients with stroke as an adjunct to standard care in an inpatient setting. Design Feasibility study. Setting Inpatient stroke rehabilitation unit at a university hospital. Participants Thirty-eight patients admitted to a stroke rehabilitation unit with upper limb motor impairment were enrolled in the ART program facilitated by trained n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…Among the included studies, 11 categorized the interventions under the domain of Art Therapy, 18,19,[24][25][26][27][28][29][30][31][32] while six studies are categorized under Occupational Therapy. 10,17,[20][21][22][23] These creative activity interventions are also named "creative art-based activities," "group interactive art therapy," "visual arts", "handicraft activities," "handicraft training," or "manual training."…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Among the included studies, 11 categorized the interventions under the domain of Art Therapy, 18,19,[24][25][26][27][28][29][30][31][32] while six studies are categorized under Occupational Therapy. 10,17,[20][21][22][23] These creative activity interventions are also named "creative art-based activities," "group interactive art therapy," "visual arts", "handicraft activities," "handicraft training," or "manual training."…”
Section: Resultsmentioning
confidence: 99%
“…Implementation unit: In Art Therapy, nine studies reported units of implementation for creative activities, with 63.6% (n = 11) were group-based 19,[25][26][27][28][29][30] and 18.2% (n = 11) were individual-based. 18,31 In Occupational Therapy, only three studies reported the implementation unit, with 33.3% (n = 6) were group-based 10,23 and 16.7% (n = 6) were individualbased. 21 These diverse approaches are influenced by various factors, such as research objectives, participant needs, and research feasibility.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations